Industrial automation : hands-on - Lamb, Frank (New York : McGraw-Hill Education, 2013)
Industrial Automation: Hands-On is a single source of essential information for those involved in the design and use of automated machinery. The book emphasizes control systems and offers full coverage of other relevant topics, including machine building, mechanical engineering and devices, manufacturing business systems, and job functions in an industrial environment. Detailed charts and tables serve as handy design aids. This is an invaluable reference for novices and seasoned automation professionals alike.
Includes bibliographical references (page 345) and index.
Keywords: Automation; Automatic machinery; Manufacturing industries -- Automation